Condition Factor and Length-weight Relationship of Pond Reared Labeo rohita - Mahmood, Tariq; Mateen, Abdul; Hadyait, Muhammad Arfan (PSM Biological Research, 2019)
Labeo rohita is commercially important freshwater fish, commonly known as rohu. A total of 240 samples of Labeo rohita collected from the twelve (12) different ponds treated with 3 concentrations of n-3 fatty acid (0.3%, 0.6%, and 0.9%), 2 levels of vitamin C (0.75g/Kg and 1.5 g/Kg) and Vitamin E (300 mg/g and 600 mg/g) were investigated for condition factor and length-weight. The relationship between length and weight of Labeo rohita from fish catch was calculated between the two parameters by creating correlation and regression. Weight was highly correlated with total length in all Labeo rohita in the current study. The minimum (0.975) and maximum (0.997) values of coefficient of determination (R²) were noted in Labeo rohita collected from different ponds. Positive isometric growth was recorded in all sampled Labeo rohita of all treated ponds. The values of condition factor (K) calculated for, Labeo rohita, ranged between 0.964-1.896 in all ponds indicated the good condition of fish. It could be concluded that Labeo rohita attains more weight per unit of length in different ponds. These observed parameters were useful to evaluate the wellbeing of Labeo rohita population in the water bodies and provided useful information on fish biology for fisheries management scientifically.